A short history of Germany : 1815-1945 / by E.J. Passant, economic sections by W. O. Henderson and with contributions by C. J. Child and D. C. Watt - Henderson, W. O. (William Otto) Child, C.J.Watt, Donald; Passant, Ernest James
Bibliografía: p.237-244. Indice